Postexercise Dietary Protein Ingestion Increases Whole-Body Leucine Balance in a Dose-Dependent Manner in Healthy Children. Issue 5 (5th April 2017) - Volterman, Kimberly A; Moore, Daniel R; Breithaupt, Peter; Godin, Jean-Philippe; Karagounis, Leonidas G; Offord, Elizabeth A; Timmons, Brian W
Abstract: Background: Protein ingestion is important in enhancing whole-body protein balance in children. The effect of discrete bolus protein ingestion on acute postexercise recovery has yet to be determined. Objective: This study determined the effect of increasing doses of ingested protein on postexercise whole-body leucine balance in healthy, active children. Methods: Thirty-five children (26 boys, 9 girls; age range: 9–13 y; weight mean ± SD: 44.9 ± 10.6 kg) underwent a 5-d adaptation diet (0.95 g protein ⋅ kg −1 ⋅ d −1 ) before performing 20 min of cycling 3 times with a concurrent, primed, constant infusion of [ 13 C]leucine. After exercise, participants consumed an isoenergetic beverage (140 kcal) containing variable amounts of bovine skim-milk protein and carbohydrates (sucrose) (0, 5, 10, and 15 g protein made up with 35, 30, 25, and 20 g carbohydrates, respectively). Blood and breath samples were taken over the 3 h of recovery to determine non–steady state whole-body leucine oxidation (LeuOX ) and net leucine balance (LeuBAL ). Results: LeuOX (secondary outcome) peaked 60 min after beverage ingestion and demonstrated a relative dose-response over the 3 h of recovery (15 g = 10 > 5 > 0 g; P < 0.001). LeuBAL (primary outcome) demonstrated a dose-response over the 3 h [15 g (24.2 ± 8.2 mg/kg) > 10 g (11.6 ± 4.3 mg/kg) > 5 g (5.7 ± 1.9 mg/kg) > 0 g (−3.0 ± 1.7 mg/kg); all P < 0.01] with all conditions different from zero (all P < 0.001). Conclusions: Over the 3-h postexercise period, LeuBAL was negative with carbohydrate ingestion alone; however, the co-ingestion of carbohydrates and 5 g high-quality dietary protein was sufficient to promote a positive postexercise whole-body protein balance in healthy, active children. Moreover, LeuBAL increased in a dose-dependent manner within the protein range studied. Children should consider consuming a source of dietary protein after physical activity to enhance whole-body anabolism. This trial was registered at clinicaltrials.gov as NCT01598935.